Challenges in Competition Law Enforcement Against Data Monopoly in Indonesia's Digital Economy - Nada Ulya Qinvi; Nurul Laylan Hsb (Justice Law Review, 2025)
The rapid development of the platform economy has positioned data as a strategic asset that determines competitiveness. However, the massive data control by large-scale digital platforms raises concerns about data monopoly practices that may hinder innovation and create barriers to market entry. Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition was enacted before the digital economy era; thus, the relevance of its norms needs to be reassessed in addressing big data issues. This research aims to analyze the qualification of massive data control as a dominant position and formulate adaptive competition law policy recommendations in the digital era. The research methodology employed is normative juridical with a statute approach, conceptual approach, and comparative approach. The research findings indicate that normatively, massive data control can be qualified as a dominant position because it creates market dependency and network effects. Data monopoly in the platform economy requires a new legal approach that is not solely based on price indicators but also on data accessibility. Legal policies are needed to incorporate Digital Market Power clauses in the revision of the Competition Law. This includes dominant position criteria measured not only by market share but also by massive data control and user dependency on the platform.